Corporate Governance: The role of independent directors - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
Companies in Singapore may now have to spend more time and resources to look for independent directors for their firms after the recent revised Corporate Governance Code, but the efforts will be worth it, said Jeremy Goh, associate professor of finance at SMU at a panel discussion during the 3rd Singapore Corporate Governance Week.